Visualizing calculus by way of maple : - Taraporevala, Arnavaz P. (McGraw-Hill, 2012)
This book just goes through a list of examples of typical calculus problems using Maple. Unfortunately, it does not offer any insights into Maple that you could not get quickly and for free through the Maple Portal website. I gave it three starts because there are things one can learn from it, but too much material was included (calculus material) and that limits the usefulness of the book as a source of Maple skills for a student using it as a supplement.